Characterization of Fresh Bovine Amnion Membrane Combined with Hydroxyapatite as Candidate Scaffold for Alveolar Bone Tissue Engineering - Octarina, Octarina; Munadziroh, Elly (Journal of Dentistry Indonesia, 2024)
Objective: This research aims to analyze the characteristics of a BAM-HA biocomposite with ratios of 4:1 and 4:2. Methods: This research is an in vitro laboratory experiment that starts by grinding fresh BAM to produce amnion slurry and then, adding HA powder to the slurry and carrying out freeze-drying on the slurry. Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscope-Energy dispersive X-ray (SEM-EDX) tests are used to analyze the characteristics of the BAM-HA biocomposite. Results: The FTIR test results showed that the BAM-HA biocomposite had amide functional groups I, II, III, A, B, OH, CO32-, and PO43-. SEM test results showed revealed different types of pores on the surface of the biocomposite with ratios of 4:1 and 4:2. The elements C, O, Na, Mg, Si, P, CL, Ca, and Nb were found in the BAM-HA biocomposite following testing by SEM-EDX. Conclusion: Based on the research results, this research has succeeded in combining BAM-HA. The ratio BAM-HA 4:2 has the potential as a scaffold for alveolar bone tissue.